THU0474 A cross-sectional study into the effectiveness of the fibromyalgia rapid screening tool for detecting fm in patients with chronic arthritis undergoing full and tapered biological disease-modifying antirheumatic drug therapy. (15th June 2017) - Valor, L; Hernández, D Flόrez; del, T Río; Janta, I; Barrio, J Martínez; Ovalles, JG B.; Serrano, B; González, R Benítez; Tenorio, C Sáenz; Nieto, JC; González, C; Monteagudo, I; et al.
Abstract : Background: The determination of fibromylagia (FM) in patients presenting diffuse, chronic arthritis is fraught. The Fibromyalgia Rapid Screening Tool (FiRST) is a validated questionnaire with high sensitivity and moderate specificity shown to be able to identify up to 89% of FM cases, even when accompanied by anxiety, depression or functional disability. Decisions to embark upon a course of full or tapered biological disease-modifying antirheumatic drugs (bDMARD) are influenced in part by patient self-assessment scores as well as concomitant pathologies. Objectives: To evaluate the prevalence of FM using the FiRST questionnaire in bDMARD-treated chronic arthritis patients. Methods: This cross-sectional study included 325 patients [178 (54, 8%) females and 147 (45, 2%) males] diagnosed with chronic arthritis and treated with bDMARD. Patients were consecutively recruited from the Biological Therapy Unit from January to March 2015 all having undergone full or tapered bDMARD for at least 1 year. Dosage tapering had been applied to patients considered to be in remission. All patients self-completed the FiRST questionnaire with a score>5/6 considered positive. Clinical assessment was carried out by one specialist only. Demographic, clinical and laboratory variables were recorded with pathology-specific indices used to assess disease status, i.e.DAS28-ESR, DAS28-CRP, SDAI, CDAI, BASDAI, BASFI, ASDAS-CRP. Patient pathologies were classified as peripheral arthritis (PerAR: RA, PsA, PerSpA) or axial spondyloarthropathy type (AxSpA). Results: A total of 68/325 (21%) patients scored >5/6 in the FiRST. Disease duration and previous bDMARD usage were not significant regarding scores <5/6. In the PerAR vs. AxSpA group, we observed that 19% (n=43) and 35% (n=25) scored FiRST>5/6, respectively (p=NS). Fifteen per cent of patients with tapered bDMARD registered scores >5/6 against 85% of patients in full bDMARD dosage (p=0.001). There were a higher number of remission patients in the PerAR group as defined under DAS28-ESR, SDAI and CDAI [(96%, 94% and 94%) (p=0.01, p=0.04, p=0.032), respectively]. Association was found in the PerAR subgroups between tapered bDMARD and remission in RA patients only, as defined under DAS28-VSG, SDAI and CDAI (p=0.026, p=0.04, p=0.043, respectively). In the AxSpA tapered bDMARD subset, 86% of patients were considered to be in clinical remission as set out under BASDAI (p=0.019). Conclusions: No difference was observed between the PerAR and AxSpA groups for FiRST>5/6. Fewer patients undergoing tapered bDMARD dosage recorded FiRST scores >5/6. Therefore, early identification of chronic arthritic patients presenting FiRST>5/6 may prove to be an important step in furthering understanding of clinical activity in diffuse arthritis as well as offering improved diagnostic and therapeutic outcomes to bDMARD-treated patients with possible concomitant FM. Disclosure of Interest: None declared